Corporate Governance, Corporate Social Responsibility and Firm Value: Economic Value Added as the Intervening Variable - Rahayu, Isti; Anggraeni, Desti (Proceeding UII-ICABE, 2020)
This research study is aimed to find out whether Economic Value Added (EVA) mediates the relationship between Good Corporate Governance (GCG) and firm value, and mediate the relationship between Corporate Social Responsibility (CSR) and firm value. The sample used in this research is mining sector companies listed on the Indonesia Stock Exchange during the period 2013-2017. The statistical method used is multiple linear regression with path analysis to solve the mediate variable. The research findings revealed that EVA does not mediate the relationship between GCG and firm value, and does not mediate the relationship between CSR dan firm value. Although EVA does not serve as the mediator, it influences firm value. Keywords: GCG, CSR, EVA, firm value, mining companies.